(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
This work demonstrates certain standard fixed point theorems on complex-valued fuzzy metric spaces. We show certain fixed point findings in the situation of complex-valued fuzzy metric spaces, inspired by Singh et al. [25]. To begin, we extend some well-known existing conclusions from metric spaces to complex-valued fuzzy metric spaces and then prove them in the complex-valued complete fuzzy metric space context. We provide an example that supports our main result and supports our hypotheses.